Participants’ awareness of ethical compliance, safety and protection during participation in pharmaceutical industry clinical trials: a controlled survey - González Saldívar, Gerardo; Rodríguez Gutiérrez, René; Viramontes Madrid, José Luis; Salcido Montenegro, Alejandro; Alvarez Villalobos, Neri Alejandro; González Nava, Victoria; González González, José Gerardo (2019)
Background: The rapid increase of industry-sponsored clinical research towards developing countries has led to potentially complex ethical issues to assess. There is scarce evidence about the perception of these participants about the ethical compliance, security, and protection. We sought to evaluate and contrast the awareness and perception of participants and non-participants of industry-sponsored research trials (ISRT) on ethical, safety, and protection topics. Methods: A Cases-control survey conducted at twelve research sites in México. Previous and current participants of ISRT (cases) as well as non-participants (controls) with one of four chronic diseases, were asked to complete the survey which focused on ethical compliance and protection issues of ISRT, and the perception of participating in a trial. Results: A total of 604 cases and 604 controls were surveyed. Cases significantly answered that ethics committees are aware of what is happening in studies (50.5% vs. 33.8%, P=≤ 0.001), and that medical care of industry-sponsored research trials is better than their usual medical care (77.2% vs. 38.2%, P=<0.001).Thesameproportionofcasesand controls thought patients must receive economical reimbursement for participating in a research study (49.5% vs. 53.1%, P=0.205). The informed consent of the pharmaceutical clinical trial was fully read by 90.4% of the cases. Most cases were satisfied or very satisfied with their overall study participation (35.6 and 62.3%, respectively). Conclusion: Previous and current participants of industry-sponsored research trials have a more positive attitude towards ethics committees, the quality of medical care of the research trials, and the main purpose of economical reimbursements, when compared to non-participants. Keywords: Good clinical practices, Perception, Clinical trials, Pharmaceutical industry, Ethics committees